Polyunsaturated fatty acids in emerging psychosis: a safer alternative?. Issue 3 (27th May 2014) - Schlögelhofer, Monika; Amminger, G. Paul; Schaefer, Miriam R.; Fusar‐Poli, Paolo; Smesny, Stefan; McGorry, Pat; Berger, Gregor; Mossaheb, Nilufar
Abstract Aim A promising approach of indicated prevention in individuals at increased risk of psychosis was based on the finding of potential neuroprotective properties of omega‐3 polyunsaturated fatty acids (PUFAs). Considering the rising interest in omega‐3 PUFA supplementation as preventive treatment strategy in young people at risk of psychosis, the question of safety issues must be addressed. Methods For this systematic review, a literature search for studies on omega‐3 PUFAs for emerging psychosis with a focus on the safety profile was undertaken. Because limited data are available, information regarding potential side effects of omega‐3 PUFAs was additionally derived from currently available data in psychotic disorders at different stages of the illness. Furthermore, helpful evidence from somatic disorders and healthy controls was used. Results In terms of safety issues, evidence from the randomized controlled trial in ultra‐high‐risk individuals and a variety of studies in schizophrenia patients strongly suggests that omega‐3 PUFAs are safe and well tolerated even when used in relatively high doses. Most commonly occurring but clinically rarely significant are mild gastrointestinal symptoms; similarly, the slight risk of prolonged bleeding time has not been shown to be clinically relevant. Differential effects on metabolic parameters, most of which appear beneficial, have been reported. Conclusions Taken together, one promising aspect of omega‐3 PUFAs is that there seem to be no reports of relevant deleterious side effects in humans, even at high doses. The differential effects on lipid parameters and bleeding time are noteworthy and need further clarification.